Hubungan Kecerdasan Emosi Dengan Tekanan Kerja Dalam Kalangan Pekerja Sektor Pembinaan - Zaharudin, Muhammad Zarul Fitri; Masrom, Md Asrul Nasid; Sarpin, Norliana; Md Yassin, Azlina; Safri, Sahrizal (Research in Management of Technology and Business, 2023)
The problem of stress at work can affect workers in any sector and this problem is becoming more prevalent nowadays. In Malaysia, the construction sector also faces the same problem among their employees. Work pressure is significantly contributing to a negative impact on an organization. Therefore, this study aims to examine the level of emotional intelligence and the factors that cause work stress among workers in the construction sector to identify the relationship between emotional intelligence and work stress among workers in the construction sector. This study is a quantitative study using the survey questionnaire method.  The results were analyzed using the Statistical Package for Social Sciences (SPSS) application to obtain descriptive and correlation analysis. The respondents in this study were 100 construction project workers and they provided information based on the questions stated in the questionnaire. The results of the study found that the majority of respondents involved in this study agreed with all levels of emotional intelligence and work stress factors stated in this study. The results show that emotional intelligence can help understand and evaluate their emotional state indirectly. This study will contribute to the management and individuals to overcome the problem of work stress that occurs in the workplace.